Measurement of the CP-violating phase β in B0→J/ψπ+π− decays and limits on penguin effects - Aaij, Roel; Aquines Gutiérrez, Osvaldo; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Britsch, Markward; Comerma-Montells, Albert; De Cian, Michel; Dordei, Francesca; Esen, Sevda; Färber, Christian; Fontana, Marianna; et al. (Physics letters, 2015)
Time-dependent CP violation is measured in the B0→J/ψπ+π− channel for each π+π− resonant final state using data collected with an integrated luminosity of 3.0 fb−1 in pp collisions using the LHCb detector. The final state with the largest rate, J/ψρ0(770), is used to measure the CP-violating angle 2βeff to be (41.7±9.6−6.3+2.8)°. This result can be used to limit the size of penguin amplitude contributions to CP violation measurements in, for example, Bs0→J/ψϕ decays. Assuming approximate SU(3) flavour symmetry and neglecting higher order diagrams, the shift in the CP-violating phase ϕs is limited to be within the interval [−1.05°,+1.18°] at 95% confidence level. Changes to the limit due to SU(3) symmetry breaking effects are also discussed.
Im Titel sind "+", "-" und "0" hochgestellt
LHCb Collaboration: R. Aaij, O. Aquines Gutierrez, S. Bachmann, A. Bien, J. Blouw, M. Britsch, A. Comerma-Montells, M. De Cian, F. Dordei, S. Esen, C. Färber, M. Fontana, E. Gersabeck, L. Grillo, X. Han, S. Hansmann-Menzemer, A. Jaeger, M. Kolpin, K. Kreplin, G. Krocker, B. Leverington, J. Marks, M. Meissner, M. Neuner, T. Nikodem, M. Schmelling, P. Seyfert, M. Stahl, S. Stahl, U. Uwer, M. Vesterinen, S. Wandernoth, D. Wiedner, A. Zhelezov [und 666 weitere]
Gesehen am 07.04.2021